Factors That Do Not Influence Public Non-Compliance in Paying Motor Vehicle Taxes - Susena , Karona Cahya; Sarma, Dimas Titan Putra; Hidayah , Nenden Restu; Wijaya , Ermy (Utami Publisher, 2025)
Motor vehicle tax (PKB) is an important source of regional income in supporting development and public services. However, public non-compliance in paying motor vehicle taxes is still a major problem in various regions in Indonesia. This article aims to identify factors that influence people's non-compliance in paying PKB, by referring to several case examples on the internet and various previous studies. The factors that will be discussed include economic, social, cultural aspects, as well as weaknesses in the existing tax administration system. In addition, an analysis of spelling and writing errors in the references used will be carried out to provide a clearer understanding of the errors that often occur in writing articles related to motor vehicle tax.